2018
DOI: 10.3390/jcm7110410
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretching Simulates Cardiac Physiology and Pathology through Mechanosensor Piezo1

Abstract: The dynamics of a living body enables organs to experience mechanical stimulation at cellular level. The human cardiomyocytes cell line provides a source for simulating heart dynamics; however, a limited understanding of the mechanical stimulation effect on them has restricted potential applications. Here, we investigated the effect of mechanical stimulation on the cardiac function-associated protein expressions in human cardiomyocytes. Human cardiomyocyte cell line AC16 was subjected to different stresses: 5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Another, and probably the most known, stretch sensor in CMs involves the cytoskeleton and allows the process of mechanotransduction to occur at a different site from where the strain is applied (Ingber, 2003a,b). These models are supported by in vitro studies where it has been shown that the application of a mechanical stimulus to isolated CMs or stem cells results in changes in gene and protein expression that are indicative of a (patho)physiological response or cell maturation and differentiation (Vining and Mooney, 2017;Kim et al, 2018;Wong et al, 2018). A possible mechanism for this involves many different proteins ranging from the ECM molecules to membrane and intracellular proteins that bind to the cytoskeleton and orchestrate the cellular response to different microenvironments.…”
Section: Mechanosensing In Cardiac Diseasementioning
confidence: 95%
See 1 more Smart Citation
“…Another, and probably the most known, stretch sensor in CMs involves the cytoskeleton and allows the process of mechanotransduction to occur at a different site from where the strain is applied (Ingber, 2003a,b). These models are supported by in vitro studies where it has been shown that the application of a mechanical stimulus to isolated CMs or stem cells results in changes in gene and protein expression that are indicative of a (patho)physiological response or cell maturation and differentiation (Vining and Mooney, 2017;Kim et al, 2018;Wong et al, 2018). A possible mechanism for this involves many different proteins ranging from the ECM molecules to membrane and intracellular proteins that bind to the cytoskeleton and orchestrate the cellular response to different microenvironments.…”
Section: Mechanosensing In Cardiac Diseasementioning
confidence: 95%
“…However, it is likely that the same mechanosensing pathways described previously allow also the maturation of the different cultured 3D tissues. Recently, it has been shown that following mechanical stretch, Piezo1, phosphorylated-Ak transforming serine473 (P-AKTS473), and phosphorylated-glycogen synthase kinase-3 beta serine9 (P-GSK3) expression was downregulated in the human CM cell line AC16 (Wong et al, 2018). In another study, the mechanical stretch induces endothelial nitric oxide synthase gene expression in neonatal rat CMs (Cheng et al, 2009).…”
Section: Mechanosensing In Tissue Regeneration and Modelingmentioning
confidence: 98%
“…• Demonstrates that hypoxia modulates the PP2A system What is the clinical significance (Davidson et al, 2005), and have been used as a cardiomyocyte model to study the effect of mechanical stretch and hypoxia (Lee et al, 2018;Wong et al, 2018).…”
Section: What This Study Addsmentioning
confidence: 99%
“…Piezo1 is required for maintaining arterial wall thickness, as well as calcium and transglutaminase activity in arterial smooth muscle cells of mice [21]. It has also been reported that Piezo1 modulates calcium ion levels in human cardiomyocytes [22]; however, the mechanisms involving Piezo1 and Piezo2 mechanotransduction in mammals remain unknown.…”
Section: Role Of Mechanosensor In Normal Cellsmentioning
confidence: 99%